Alternative Capital Markets Dim Sum and Sukuk market analysis - Kotoun, Karel; Krabec, Tomáš, 1981-; Hnilica, Jiří, 1976-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2015)
The aim of this paper is to study the market functionalities, explain forms of issuance, transfer and valuation of alternative financial debt instruments, CNH denominated bonds and Islamic bonds Sukuk. The utter objective is to present a well-composed model for yield calculation for these alternative financial instruments in order to provide source of information for companies before issuance.
Vedoucí práce: Tomáš Krabec
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses